X-Ray Analysis of Fluidized Beds and Other Multiphase Systems - John Yates; David Cheesman; Paola Lettieri; David Newton (KONA Powder and Particle Journal, 2014)
The attenuation of a beam of X-rays as it passes through a body has been used for over 100 years in diagnostic medicine. A more recent application of the technique has been in the study of industrial-type units such as gas-solid fluidized beds, and this paper reviews this application in the analysis of the hydrodynamic features of bubbling and circulating fluidized beds. The measurement of jet penetration into bubbling beds and the study of bubble slurry columns are also considered. The equipment used and its methods of operation are described and the salient results of the more revealing investigations are summarised both from a qualitative and a quantitative viewpoint.